Performance analysis of the Japanese national 4×100 m relay team: Examination of sprinting ability and gain time - Matsubayashi, T.; Kobayashi, K.; Takahashi, K.; Yamanaka, R.; Wataya, T.; Ohnuma, H. (Journal of High Performance Sport, 2024)
This study aimed to analyze the sprinting ability and baton-exchanging technique of national 4×100 m relay teams participating in the Nassau 2024 World Athletics Relays, and to examine their relationship with the 4×100 m relay record. Additionally, this study focused on the Japanese national team to assess their current sprinting ability and baton-exchanging technique and identify areas for improvement. The 100 m record average of the four legs was used as an index of sprinting ability, while gain time, defined as the difference between the total 100 m record of the legs and the relay record, was utilized as an index of baton-exchanging technique. The 100 m record average exhibited a strong correlation with the 4×100 m relay record (r=0.75 in men and r=0.83 in women). Gain time was not correlated with either the 4×100 m relay record or the 100 m record average, and was similarly distributed across teams of all competition levels. The mean gain time was approximately 1.8 s for both men and women, with a standard deviation of 0.3 s. Based on these statistics, the gain time for the top 5% was estimated to be approximately 2.3 s. The men's Japanese team ranked 11th in the 100 m record average and 2nd in gain time at the World Athletics Relays, indicating sufficient sprinting ability and baton-exchanging technique to achieve a high placement at world-class competitions. The women's Japanese team ranked 24th in the 100 m record average and 4th in gain time, demonstrating a high international standard in baton exchanging technique but a significant gap in sprinting ability required for world-class competition. Improving sprinting ability was deemed essential for the women's Japanese team to compete at the world-class competitions.